2020
DOI: 10.1111/psyp.13642
|View full text |Cite
|
Sign up to set email alerts
|

Brain oscillatory activity associated with switch and mixing costs during reactive control

Abstract: Although this ancient Latin quote was not coined with reference to task-switching, a common finding in the cognitive control literature is that switching from one task to another incurs a significant "switch cost" as compared to repeating the same task. Yet, there is also a "mixing cost" when contrasting performance on the all-repeat trials from the single-task blocks and the repeat trials from the mixed blocks (Monsell, 2003; Rubin & Meiran, 2005). The switch cost is generally taken as an index of a phasic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…During the preparatory (cue-test stimuli) interval, these patterns of modulation of cortical oscillations are more elevated for switch compared to repeat trials. Similar results have also been reported in a task using simultaneous cues and test stimuli ( Capizzi et al, 2020 ). The higher increase in theta band activity following the cue onset in switch trials is believed to reflect neuronal activity associated with proactive goal-updating processes ( Cooper et al, 2017 ) and increased cognitive control ( Cavanagh and Frank, 2014 ) required by shifts of attention.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…During the preparatory (cue-test stimuli) interval, these patterns of modulation of cortical oscillations are more elevated for switch compared to repeat trials. Similar results have also been reported in a task using simultaneous cues and test stimuli ( Capizzi et al, 2020 ). The higher increase in theta band activity following the cue onset in switch trials is believed to reflect neuronal activity associated with proactive goal-updating processes ( Cooper et al, 2017 ) and increased cognitive control ( Cavanagh and Frank, 2014 ) required by shifts of attention.…”
Section: Introductionsupporting
confidence: 88%
“…The task used in our study requires the execution of a motor response according to a stimulus–response contingency that depends on the attended stimulus feature, while inhibiting the neuronal representation of the conflicting stimulus–response contingency used in previous trials. The stronger suppression of beta band activity in switch versus repeat trials observed in our study and others ( Cunillera et al, 2012 , Foxe et al, 2014 , Capizzi et al, 2020 ) may be explained based on two premises. First, beta band oscillations in prefrontal regions may reflect activity in competitive neuronal ensembles encoding the stimulus–response contingencies corresponding to alternative rules ( Buschman et al, 2012 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Further studies involving iEEG oscillations other than high-gamma activity are warranted to determine the network dynamics supporting cognitive flexibility. Prior scalp EEG studies reported that the theta amplitude and coherence across frontal and parietal regions differed between switch and repeat trials ( Cooper et al, 2015 ; Capizzi et al, 2020 ; McKewen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed mixing and switching costs as markers of sustained and phasic control processes, respectively. We also manipulated cue-to-target interval (CTI: 300 vs. 1200 ms) on a trial-by-trial basis to differentially modulate cognitive demands in this paradigm (e.g., Meiran 1996 ; Cooper et al 2015 ; Capizzi et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%